Basal Cell Carcinoma in Elderly Women - Idris, Irma Suryani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Basal cell carcinoma (BCC), previously referred to as basal cell epithelioma, this is the most prevalent cancer in people. Rarely can BCC form on mucosal membranes or on the palms and soles; it usually appears on sun-damaged skin. Metastasis is uncommon in basal cell carcinoma, which typically grows slowly. BCC is rarely lethal, but when therapy is insufficient or delayed, it can be extremely damaging and damage local tissue. BCC typically manifests clinically as a pink or flesh-colored pearly papule with telangiectatic or ulcerated arteries. Although it can also affect the limbs, BCC usually affects the head or face. Case report: A 70-year-old woman came to the dermatovenerology polyclinic in Makassar city with complaints of a lump on her nose that had been getting bigger and sometimes bleeding. The size of the tumor lesion was about 1.5 cm, excision of the lesion was performed under local anesthesia considering that there was impaired lung function from the chest X-ray. Follow-up 5 days before wound closure while waiting for the biopsy results, bleeding was minimal and the biopsy results showed pigmented basal cell carcinoma with tumor-free edges. Closure of excision wound with simple suture showed good suture viability, without signs of tissue necrosis or infection at the previous lesion site. Treatment of basal cell carcinoma (BCC) is highly dependent on the anatomical location and histologic characteristics of the lesion. Excision was performed due to its high-risk location on the face.